The Effect of Genre-Based Approach and Canva on Descriptive Writing Skills - Mila Aruna; Angelia Cipta Riska Nabella; Noor Malihah (CV. Rayyan Dwi Bharata, 2026)
Writing remains one of the most challenging language skills for English as a Foreign Language (EFL) learners. This study aims to explore the impact of combining the Genre-Based Approach (GBA) with Canva-based educational media on students' descriptive writing skills at various levels of learning motivation. Using a quantitative method with a 2 × 2 factorial quasi-experimental framework, this study included 30 eighth-grade students from SMPIT Al Falah Simo during the 2025/2026 academic year. The experimental treatment group (n=11) was taught using GBA integrated with Canva, while the control group (n=19) underwent traditional teaching methods. Data were collected through pre- and post-study writing assessments, along with a 17-item learning motivation survey, and analysed using Two-Way ANOVA. The results showed that the teaching strategy did not significantly affect independent writing skills (Sig. = 0.371 > 0.05). On the other hand, learning motivation had a significant impact on writing outcomes (Sig. = 0.000 < 0.05). Importantly, a significant interaction effect was identified between learning strategies and learning motivation levels (Sig. = 0.045 < 0.05). This indicates that GBA combined with Canva significantly improves descriptive writing skills, especially when addressed to highly motivated students.